2018
DOI: 10.1016/j.ijid.2018.04.798
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of ST5-II-t311 clone among healthcare-associated methicillin-resistant Staphylococcus aureus isolates recovered from Zhejiang, China

Abstract: CC5/ST5-MRSA-II-t311 has become the predominant HA-MRSA clone in Hangzhou, Zhejiang Province. ST59 MRSA has spread into hospitals. The isolates showed good susceptibility to all five anti-MRSA agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Egyir et al [48] reported this clone as one of the predominant clones among healthcare institutions in Ghana. It is also reported as one of the predominant clones causing blood stream infections in Europe [58,59], Asia [60,61] and South America [62].…”
Section: Source (N)mentioning
confidence: 99%
“…Egyir et al [48] reported this clone as one of the predominant clones among healthcare institutions in Ghana. It is also reported as one of the predominant clones causing blood stream infections in Europe [58,59], Asia [60,61] and South America [62].…”
Section: Source (N)mentioning
confidence: 99%
“…ST59 was a major CA-MRSA and the second common MRSA in ours results. Our nding indicated the distinctions between CA-MRSA and HA-MRSA isolates have become blurred and they could be a mutual integration 29 . Previous studies indicated that ST59 MRSA might spread into hospital from community 29,33 .…”
Section: Discussionmentioning
confidence: 79%
“…ST5-II MRSA (NEW York/Japan) clone was one of the most predominant genotypes in many countries 27,28 . Also, previous study showed that ST5 was the predominant HA-MRSA clone in Zhejiang, China from 2012 to 2013 29 . Moreover, some investigators have expressed different opinions on the most main spa type of ST5.…”
Section: Discussionmentioning
confidence: 94%
“…Zhejiang, Guangdong, and Guangxi [15][16][17][18]. To date, however, no study has focused on the molecular characteristics and virulence gene profiles of S. aureus isolates in Hainan, and no hospital in Hainan has been included in any multi-center studies concerned with those characteristics of S. aureus in China [13,19,20].…”
mentioning
confidence: 99%